Terorisme di Aceh: Studi Analisis Sosial-Budaya Tentang Penolakan Masyarakat Aceh Terhadap Gerakan Radikal Tandhim Al Qaidah Serambi Makkah - Apridar, Apridar; Subhani, Subhani; Chaidar, Al (PASAI, 2014)
Issues raised in this study are: what and how the terrorist movement could emerge in Aceh which are known to have a different Islamic characteristics? This study will examine how the transformation of ideological belief within the Acehnese to accept and/or to reject the radical Islamic movements that have been entered and began to spread in Aceh. This study will focus on the analysis of the ideology of "Islam Aceh" (Achenized Islam), which is then met with radical Islamic ideology of Java; what makes them able to have a common view of the "jihad" in the region which are considered to embrace "peace with democracy" after three turbulent decades. And, in former time, Aceh attempt to secede from the Republic of Indonesia in secular means. This study also will find out any books (kitab) that have influenced the people of Aceh who took part in this terrorist movement, and also how the people of Aceh in understanding the culture puts salafiyah radical Islamic thinking that drive terrorism in Aceh. The focus of this study will look at the patterns of thinking and acting as well as the cultural elements of Aceh in the followers of terrorist movements in Aceh. Explanation of this is very important to understand why the restive Aceh take ideas that are not ethno-nationalism, as formerly occurred within the Free Aceh Movement or GAM from 1976 to 2005. A number of prisoners who were jailed in terrorism cases at Tanjung Gusta Prison, Medan and Jakarta as well as in Nusakambangan will be interviewed. So also with the inmates who come from outside Aceh who are involved in terrorism in the province will be traced why and how their interaction with the people of Aceh during the movement. The study also would like to see how and in what social, economic, political and cultural settings the "terrorist Aceh" group is to survive and develop themselves. In addition, this study will gather some qualitative views of various circles of society in Aceh on the cultural differences by then that the majority of the people of Aceh who had been contacted by the terrorists refused to participate in the terror movement in Aceh so that the terrorist group should move to North Sumatra, Riau, Jambi, Lampung, South Sumatra and East Java and Lombok.